G433(P) A child with juvenile myasthenia gravis in association with type 1 diabetes mellitus. (25th October 2020) - Woods, E; Joseph, L; Adeleye, O
Abstract : Background and Aims: Having an existing autoimmune disease predisposes to another; the underlying pathophysiology of this is unclear. Type 1 diabetes mellitus (T1DM) is an autoimmune condition which can be seen in conjunction with autoimmune thyroid disease, coeliac disease, autoimmune gastritis, vitiligo and Addison's disease. Myasthenia Gravis (MG) is one autoimmune disorder where there are very few reported cases worldwide of its coexistence with T1DM. In this case, we report a child with T1DM who later develops MG. Case Presentation: Six months after initial diagnosis of T1DM, this 7 year old child presented with ocular symptoms, dysarthria and dysphagia during acute varicella zoster infection. Investigations were all negative including AChR, anti-musk and anti-ganglioside antibodies. Despite this, a trial of pyridostigmine provided symptomatic improvement. Clinical diagnosis of juvenile myasthenia was verified when a weaning dose of pyridostigmine resulted in re-emergence of clinical symptoms. Outcome and Follow Up: This child remains on an increased dose of pyridostigmine for symptom control. Clinical diagnosis of two distinct co-existent autoimmune diseases (T1DM and MG) has now been confirmed. Discussion: This child had increased likelihood of developing other autoimmune conditions with a diagnosis of T1DM, increased further by a strong family history of rheumatoid arthritis. Thyroid endocrinopathy and coeliac disease are more commonly associated with T1DM and, as a result, are tested for at diagnosis of T1DM. Screening tests for other autoimmune conditions are not routine, however clinical vigilance in identifying other autoimmune conditions is required. Conclusion: Children with T1DM are predisposed to other autoimmune conditions including, although extremely rarely, MG. In a child with existing autoimmune disease presenting with neurological symptoms suggestive of MG, it is important to consider tests for juvenile MG, although lack of positive results does not rule out disease. The diagnosis of MG in children is largely clinical and diagnosis is usually based on response to pyridostigmine.